A Systematic Review of Surgical Robots and Controls for Teleoperations - Kojo Nyamekye Assan; Phyllis Teteki Wayoe; Christabel Naadu Ayiku; Agbemor Dzifa Aku; Herbert Quagraine (Institut Teknologi Dirgantara Adisutjipto, 2025)
The advancements in healthcare technology have transformed the landscape of medical practice, with robotics emerging as a prominent feature. The use of teleoperation, particularly in remote robot-assisted surgeries, has obtained significant attention and acclaim for its potential to enhance surgical outcomes and expand access to specialized care. Despite the increase in research in this domain, there remains a need for a thorough and systematic review to consolidate the diverse findings and conclusions. This work presents an organized synthesis of existing related works using Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA), facilitating easier access to vital information for researchers, practitioners, and innovators. To achieve this, the historical development of surgical robots were explored. Furthermore, different types of surgical robots with various architecture were extensively examined to highlight the relevance of their application. Imperatively, advancements in teleoperability and control systems of surgical robots were comprehensively discussed underscoring its growing influence in current healthcare delivery. Moreover, practical challenges faced by teleoperated surgical robots were highlighted and elaborated to point out their limitations. Additionally, future directions aimed to tackle the identified shortfalls in robotic surgery and teleoperation were considered. In this regard, this work provided an impactful contribution that positively influences growth in the area of robotic surgery and teleoperation by consolidating several insights into a cohesive framework which ultimately seek to improve patient care.